Effect of Sorted Metallic and Semiconducting Single-Walled Carbon Nanotubes on LiFePO4 Cathode Material for Lithium Ion Batteries. (25th October 2017) - Adepoju, Adewale A.; Searles, Thomas A.; Fagan, Jeffrey A.; Williams, Quinton L.
Abstract : Type sorted metallic (m) and semiconducting (s) single-walled carbon nanotubes (xSWNT) are incorporated into carbon coated LiFePO4 (cLFP) cathodes to study their effects on charging time and energy capacity. The SWNTs form a 3D conductive network which is expected to enhance the electronic mobility through percolation. Comparison tests show that the cLFP/mSWNTs cathode material delivers a slightly faster charging time than batteries made using sSWNTs. Conversely, the energy capacity is found to be higher for batteries made using sSWNTs than for those made using mSWNTs. Both battery types exhibit good cycle stability performance relative to each other.